NOGAPS-ALPHA model simulations of stratospheric ozone during the SOLVE2 campaign - McCormack, J. P.; Eckermann, S. D.; Coy, L.; Allen, D. R.; Kim, Y.-J.; Hogan, T.; Lawrence, B.; Stephens, A.; Browell, E. V.; Burris, J.; McGee, T.; Trepte, C. R. (Atmospheric Chemistry and Physics, 2004)
This paper presents three-dimensional prognostic O3 simulations with parameterized gas-phase photochemistry from the new NOGAPS-ALPHA middle atmosphere forecast model. We compare 5-day NOGAPS-ALPHA hindcasts of stratospheric O3 with satellite and DC-8 aircraft measurements for two cases during the SOLVE II campaign: (1) the cold, isolated vortex during 11-16 January 2003; and (2) the rapidly developing stratospheric warming of 17-22 January 2003. In the first case we test three different photochemistry parameterizations. NOGAPS-ALPHA O3 simulations using the NRL-CHEM2D parameterization give the best agreement with SAGE III and POAM III profile measurements. 5-day NOGAPS-ALPHA hindcasts of polar O3 initialized with the NASA GEOS4 analyses produce better agreement with observations than do the operational ECMWF O3 forecasts of case 1. For case 2, both NOGAPS-ALPHA and ECMWF 114-h forecasts of the split vortex structure in lower stratospheric O3 on 21 January 2003 show comparable skill. Updated ECMWF O3 forecasts of this event at hour 42 display marked improvement from the 114-h forecast; corresponding updated 42-hour NOGAPS-ALPHA prognostic O3 fields initialized with the GEOS4 analyses do not improve significantly. When NOGAPS-ALPHA prognostic O3 is initialized with the higher resolution ECMWF O3 analyses, the NOGAPS-ALPHA 42-hour lower stratospheric O3 fields closely match the operational 42-hour ECMWF O3 forecast of the 21 January event. We find that stratospheric O3 forecasts at high latitudes in winter can depend on both model initial conditions and the treatment of photochemistry over periods of 1-5 days. Overall, these results show that the new O3 initialization, photochemistry parameterization, and spectral transport in the NOGAPS-ALPHA NWP model can provide reliable short-range stratospheric O3 forecasts during Arctic winter.